2014
DOI: 10.1063/1.4894781
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pseudo-gap states on the pinning energy and irreversibility field of high temperature superconductors

Abstract: The existence of pseudo-gap states at energies larger than the coherence energy scale is shown to be at the origin of the difficulties encountered in achieving strong vortex pinning in the high Tc cuprates. Reduction or elimination of the pseudo-gap states by overdoping is effective in increasing the condensation energy and the irreversibility field. In YBa2Cu3O7, a full BCS state, with a single energy scale, can be restored, leading to the highest known irreversibility field and pinning strength. In the bismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…For instance, a recent investigation [22] of the magnetic excitations in cuprates with zero, one, or two apical oxygen per CuO 2 plane concluded that the structure without apical oxygen had the most long-range electron hopping. Likewise, any strain or distortion of the CuO 2 planes is likely to alter the pair condensation energy and its J C [3]. Hence, we consider the implications of apical V O .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, a recent investigation [22] of the magnetic excitations in cuprates with zero, one, or two apical oxygen per CuO 2 plane concluded that the structure without apical oxygen had the most long-range electron hopping. Likewise, any strain or distortion of the CuO 2 planes is likely to alter the pair condensation energy and its J C [3]. Hence, we consider the implications of apical V O .…”
Section: Resultsmentioning
confidence: 99%
“…Subtle changes in structure and stoichiometry stemming from defects influence many functional properties of ceramics. A paradigmatic example is the high-temperature superconductor YBa 2 Cu 3 O 7−x (YBCO), where its critical temperature (T c ) and critical current density (J c ) are governed by oxygen vacancies (V O ) [1][2][3]. The structure of YBCO, shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, oxygenation at low temperatures would be interesting because one can further modify the oxygen content of the YBCO films. [73][74][75][76] To overcome the low temperature limitation in the oxygenation of functional oxides, it has been shown that silver can be used as a catalyst to enhance the rate of oxygen incorporation. The use of silver as a catalyst for selective oxidation processes is well-known in different fields, especially in the hydrocarbon industry.…”
Section: View Article Onlinementioning
confidence: 99%